Substitution Errors in Jokowi’s English: A Phonological Analysis - Pretty Sayang Chalista Dewi; Ni Nyoman Deni Ariyaningsih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines substitution errors in the English pronunciation of President Joko Widodo, focusing on a speech delivered at the “ASEAN–Australia Special Summit 2018.” The research aims to describe the systematic substitution patterns that occur in his pronunciation and to explain how these are influenced by his first languages (L1), Javanese and Indonesian. Using a qualitative descriptive method, the data were collected through repeated video observation, phonetic transcription using the International Phonetic Alphabet (IPA), and comparison with standard British English pronunciations from the Cambridge Dictionary. The analysis is framed within Roach’s (1991) segmental phonology, which classifies vowel and consonant changes by articulatory features, and Brown’s (2008) theory of language transfer, which explains how L1 sound systems influence L2 production. The results show 28 recurring substitutions, such as /v/ → /f/ or /p/, /θ/ → /t/, diphthong simplification to monophthongs, vowel shifts to fit the Indonesian/Javanese five-vowel system, and hyper-articulation of weak syllables. These findings confirm that the deviations are not incidental but stem from systematic L1 interference, aligning with prior research on Indonesian EFL learners’ pronunciation challenges. This study contributes to understanding how high-profile non-native English speakers adapt segmental features in formal, international contexts, and the findings have pedagogical implications for pronunciation training, particularly in preparing speakers for contexts where intelligibility and accuracy are critical. Keywords: pronunciation errors, substitution patterns, Javanese, Indonesian, language transfer.